Capital Structure Modelling: Evidence From The Jakarta Islamic Index (JII) - Wuryaningsih Dwi Lestari; Anestia Retno Kusumastuti; Ma’ruf Ma’ruf; Wafiatun Mukharomah; Muhammad Sholahuddin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
The purpose of this study was to determine the effect of variables firm size, liquidity, profitability, tangibility, and growth opportunity on the capital structure of companies listed in the Jakarta Islamic Index (JII). This study uses secondary data in the form of financial statements from each company. The sample collection uses purposive sampling. The population in this study were companies listed in JII for the period 2008-2017 with a sample of four companies. The data analysis technique used is panel data. The results of this study indicate that firm size has no significant effect on capital structure, liquidity has a significant negative effect on capital structure, profitability has no significant effect on capital structure, while tangibility and growth opportunity have a significant negative effect on capital structure. The results of this study are expected to be a consideration for academics, companies, and investors in determining or estimating a healthty capital structure by considering variables firm size, liquidity, profitability, tangibility, and growth opportunity.